Implikasi Peran Dan Fungsi Pengawasan Bank Syariah Di Indonesia Pasca UU No. 21 Tahun 2011 - Sadillah, Ferri; Nurnasrina, Nurnasrina; Syahfawi, Syahfawi (JAWI : Journal of Ahkam Wa Iqtishad, 2023)
The growth of the Sharia banking system in Indonesia is considered a measure of Sharia's economic success. The Indonesian Sharia Banking Supervision is responsible for regulating sharia banking activities. It is important to note that this information is from a regulatory point of view. The regulation and supervision of sharia banking activities are based on amendments to Act No. 3 of 2004 on the Bank of Indonesia, No. 23 of 1999, and Law No. 21 of 2008. After the passing of OJK Act No. 21 in 2011, Indonesian banks were granted the authority to oversee Sharia banks, which were then transferred to the JSC. The Financial Services Authority was formed due to concerns from various parties about the supervisory function of Indonesian banks in regulating Sharia banking. The JSC does not directly monitor all activities of Sharia institutions, but rather ensures that certain aspects are overseen by other institutions, such as the DPS (Dewan Pengawas Syariah).  The DPS is responsible for overseeing Sharia Financial Institutions, and is registered based on the approval of the National Sharia Council (DSN). The objective of the OJK is to meet and protect the needs and interests of the public, create a stable and sustainable financial system, and implement a financial system based on the principles of good governance, which include accountability, transparency, and independence.